Mixed Farming Innovations Transforming the Lives of Women Farmers in Bangladesh - Sada, Bushra Humaira; Haque, Abdul; Miajy, Abdullah; Ahmed, Sharif; Bhandari, Humnath (International Rice Research Institute, 2024)
This article highlights how The CGIAR Initiative on Mixed Farming Systems empowers Bangladeshi women farmers through innovations like crop diversification, homestead farming, and climate-smart practices. These efforts improve livelihoods, nutrition, and incomes, fostering resilience and community progress.